Inhibition of Bromodomain and Extra Terminal (BET) Domain Activity Modulates the IL-23R/IL-17 Axis and Suppresses Acute Graft-Versus-Host Disease - Snyder, Katiri J.; Choe, Hannah K.; Gao, Yandi; Sell, Natalie E.; Braunreiter, Kara M.; Zitzer, Nina C.; Neidemire-Colley, Lotus; Kalyan, Sonu; Dorrance, Adrienne M.; Keller, Andrea; Mihaylova, Maria M.; Singh, Satishkumar; et al. (Frontiers in Oncology, 2021)
Acute graft-versus-host disease (GVHD) is the leading cause of non-relapse mortality following allogeneic hematopoietic cell transplantation. The majority of patients non-responsive to front line treatment with steroids have an estimated overall 2-year survival rate of only 10%. Bromodomain and extra-terminal domain (BET) proteins influence inflammatory gene transcription, and therefore represent a potential target to mitigate inflammation central to acute GVHD pathogenesis. Using highly potent and selective BET inhibitors PLX51107 and PLX2853, we show that BET inhibition significantly improves survival and reduces disease progression in murine models of acute GVHD without sacrificing the beneficial graft-versus-leukemia response. BET inhibition reduces T cell alloreactive proliferation, decreases inflammatory cytokine production, and impairs dendritic cell maturation both in vitro and in vivo. RNA sequencing studies in human T cells revealed that BET inhibition impacts inflammatory IL-17 and IL-12 gene expression signatures, and Chromatin Immunoprecipitation (ChIP)-sequencing revealed that BRD4 binds directly to the IL-23R gene locus. BET inhibition results in decreased IL-23R expression and function as demonstrated by decreased phosphorylation of STAT3 in response to IL-23 stimulation in human T cells in vitro as well as in mouse donor T cells in vivo. Furthermore, PLX2853 significantly reduced IL-23R+ and pathogenic CD4+ IFN+ IL-17+ double positive T cell infiltration in gastrointestinal tissues in an acute GVHD murine model. Our findings identify a role for BET proteins in regulating the IL-23R/STAT3/IL-17 pathway. Based on our preclinical data presented here, PLX51107 will enter clinical trial for refractory acute GVHD in a Phase 1 safety, biological efficacy trial.